Sars-Cov-2 RNA and Spesific Antibodies in Breast Milk, Should Mother Breastfeeding? : A Literature Review - Kalista Riski Sulistyaningsih; Dwi Izzati (Universitas Andalas, 2022)
Introduction: Covid-19 is becoming a serious problem worldwide. The spread of disease occurs very quickly, viral mutations are fast and massive. Rules and guidelines change rapidly. WHO and UNICEF recommend exclusive breastfeeding, even though mothers are confirmed because the benefits are considered greater than the risks. The aim of this study are to answer questions, about whether this virus can transmit vertically through breast milk, and how to properly guide the breastfeeding process in the pandemic. Methods: The source of this literature review is accessed through Scopus, PubMed, and various reputable websites published in 2019-2021. Article search by keyword usage, inclusion criteria and exclusion. Results: 508 articles filtered to prove that the source used is viable and relevant, finally determined 12 articles. The prevalence of Covid-19 incidence in neonates from confirmed mothers was reported in some studies but there is no evidence that transmission is vertical through breast milk. SARS-CoV-2 RNA is found in some reports but there is nothing to confirm whether it is an active virus or just remnants of RNA that cannot infect. Beside RNA, Sars-Cov-2 specific antibodies were also found to protect neonates. Conclusion: Active transmission of Covid-19 vertically from breast milk has not been detected, should not be an indication of formula feeding or separation baby with mother. The findings of IgA, IgG, and IgM-specific antibodies can be passive protection, because until now no vaccination has been recommended for neonate groups.